MANAJEMEN PERENCANAAN MATERI PEMBELAJARAN KITAB KUNING BAGI SANTRI KELAS TIGA DAYAH MUDI MASJID RAYA SAMALANGA KABUPATEN BIREUEN - Ishak Ishak; Mesiono Mesiono (PIONIR: JURNAL PENDIDIKAN, 2021)
The yellow book material is an important component in a dayah (Islamic boarding school). The yellow book learning material is a program developed in the dayah (Islamic boarding school), both salafi and khalafist dayahs. And to carry out the process of planning the yellow book learning material, the dayah needs to make an efficient plan. This study discusses the management of the yellow book learning planning for the third grade students of the MUDI Dayah Great Mosque of Samalanga, Bireuen Regency. So the author examines, first; the yellow book learning material planning system for the third grade students of the MUDI Masjid Raya Samalanga, second grade; planning method for delivering yellow book learning materials for third grade students of the MUDI Dayah Masjid Raya Samalanga, third; planning evaluation of yellow book learning materials for third grade students of the MUDI Dayah Masjid Raya Samalanga. In this study, the author uses a qualitative type of research that is a phenomenological descriptive analysis with a management approach to the planning of the MUDI dayah institution at the Samalanga Grand Mosque. The research subjects were purposively sampling where the interviewees were only the head of the curriculum, the head of the MUDI Mesjid Raya Dayah education sector, the third grade teacher/guardian, and the third grade student. The results of the first research; shows that the planning system for the yellow book learning material for the third grade students of Dayah MUDI Masjid Raya Samalanga is in accordance with the education level of the third grade students. Where the yellow book learning material is clearly visible based on the results of interviews and documentation that already exists and is neatly arranged, the yellow book that is determined is very systematic according to the education level of third grade students. Second, the form of the yellow material delivery planning method for third grade students consists of the syafahi/bandongan method, the sima'ie/sorongan method and the bahsul matsail. Where the three methods are used by the teacher in delivering the yellow book learning material for third grade students at the MUDI Dayah of the Samalanga Grand Mosque. Third, to determine the ability of students to read the yellow book learning material for third grade students at the MUDI Dayah of the Samalanga Grand Mosque, it can be known through evaluation. Planning the evaluation of the yellow book learning material for third grade students at the MUDI dayah in one year is carried out three times in three semesters. In each semester, the evaluation is scheduled for fifteen days with three examiners, each examiner overseeing the exam for five days. Then for the third grade in particular, the evaluation schedule has three additional days to evaluate the material of the Alfiah temple memorizing book with a supervisor teacher who has been determined by the dayah curriculum.